Acquisition of Practical Skills in Domestic Electrical Installation: Computer Simulation Versus Demonstration Approach - Nwineh, Legborsi; Okwelle, & Paulinus Chijioke (Journal of Technical Education and Training, 2018)
The study aimed to compare transfer of knowledge of domestic electrical installation acquired through two instructional approaches: a computer simulation instructional package called â€œwiremanâ€ and demonstration instructional approach for year two students of Vocational and Technical Education in a university in Nigeria. The study is based on the theory of identical elements. Adopting post-test-only control group design, the researchers post-tested 34 students taught using wireman and 34 students taught using demonstration teaching method with a 40-item domestic electrical installation competency checklist which was faced validated by three experts and subjected to Kuder-Richardson 20 formula to achieve an internal consistency reliability coefficient of .84. One research question and one hypothesis guided the study. The research question was answered using mean statistic. The hypothesis was tested using independent t-test at .05 alpha level of significance. Result showed that students taught with the wireman approach performed better than students taught with demonstration approach. It was therefore concluded that simulated instruction with wireman was effective in practical skill acquisition in domestic electrical installation for the participating students. Based on the result of the study, using simulation for instruction in domestic electrical installation is recommended.